2013
DOI: 10.3109/14767058.2013.784737
|View full text |Cite
|
Sign up to set email alerts
|

The interconnections between maternal and newborn health – evidence and implications for policy

Abstract: The past decade has witnessed increasing global attention and political support for maternal, newborn and child health. Despite this increased attention, actual progress has been slow and sporadic: coverage of key maternal and newborn health interventions remains low and there are wide disparities in access to care, within and across countries. Strategies for improving maternal and newborn health are closely linked, and can be delivered most effectively through a continuum of care approach. While these interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 255 publications
1
73
0
1
Order By: Relevance
“…Previous research has suggested that infants who have lost their mothers have significantly higher risks of death and disease well into childhood and that maternal death also has an adverse effect on other siblings and on the extended family. 15,[28][29][30]32,33 Our study is a prospective, international, population-based research to assess the relationship between maternal and perinatal deaths. This study has several strengths.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that infants who have lost their mothers have significantly higher risks of death and disease well into childhood and that maternal death also has an adverse effect on other siblings and on the extended family. 15,[28][29][30]32,33 Our study is a prospective, international, population-based research to assess the relationship between maternal and perinatal deaths. This study has several strengths.…”
Section: Discussionmentioning
confidence: 99%
“…It may have resulted from the high proportion (24%) of women with prolonged or obstructed labour, as many of these neonates may have suffered from prolonged asphyxia in utero, complicating effective resuscitation. Referral delays may also be implicated, 26,27 as 70% of all women delivering at CURGO were out-of-district referrals. However, extant evidence suggests that delays in the ambulance networks were minimal.…”
Section: Discussionmentioning
confidence: 99%
“…While caesarean sections for breech improve perinatal mortality, 27 only 69% of neonates in breech position were delivered by caesarean section. Birth resuscitation may also not have been performed effectively or in a timely fashion in all cases.…”
Section: Public Health Action Neonatal Care and Mortality In Rural Bumentioning
confidence: 99%
“…1 Maternal morbidities such as anemia, fistula, uterine rupture and scarring, and genital and uterine prolapse also represent significant global burdens. 2 To reduce maternal and newborn morbidity and mortality, high coverage of maternal health interventions needs to be matched with overall improvements in quality of maternal health care. Health facilities and their staff play a key role in this effort.…”
Section: Introductionmentioning
confidence: 99%